Integrating physical and virtual game-based simulation for operators' training to enhance learning effectiveness: an application in hazardous industrial spaces. (22nd June 2021) - Longo, Francesco; Padovano, Antonio; Gazzaneo, Lucia; Mirabelli, Giovanni; Ferraro, Alessandra; Pirozzi, Marco; Donato, Luciano Di
Inadequate training and lack of risk awareness are among the main causes of work-related accidents in industrial facilities. Although new learning methods, such as virtual reality (VR), have been deployed, they still do not find implementation on a large-scale. This research proposes the concept of 'virtual training pills' (VTP), i.e. delivering learning content in the form of short educational games by using a common technological platform based on virtual, interactive and immersive reality. An application study has been conducted in the case of a decommissioned nuclear power plant, which is classified as confined and pollution-suspected space. These areas represent a challenging environment for maintenance and inspection activities. The results proved the potential of this novel game-based learning approach: short 'learning pills' are much more effective than long role-playing games. This work also discusses the benefits of workforce training based on VTP as an integration to live exercises for safety management.